Performance Evaluation of Motorized Groundnut Sheller - Adedeji, Omotade Segun; Ajuebor, F N (Journal of Agricultural Engineering, 2002)
A power operated groundnut sheller that shells groundnut by mechanical shearing and cleans the shelled seeds from chaff pneumatically was designed, fabricated and tested. To increase the shelling efficiency and capacity and to reduce breakage of the seeds as well as reduce power consumption, certain modifications were carried out after the preliminary test. The modifications included a reduction in the shelling speed, rubberisation of the rotating beaters, optimization of the concave slots and adjustments in the blower speed. The modified machine was tested to evaluate its general performance. The best performance of the sheller was achieved at 260 rpm shelling speed, 30 mm - 40 mm concave clearance, feeding rate of 150 kg (pods)/h giving an output of 80 kg seed/h. The shelling efficiency, cleaning efficiency and breakage were 98 %, 85%, and less than 5%, respectively. A blower speed between 1000 rpm - 1400 rpm is adequate for effective separation when chute sloped at 20degree to the horizontal.